MODELING OF PHOTOVOLTAIC PANELS FOR GAHARU ESSENTIAL OIL DISTILLATION SYSTEM - T Taufik; S Subhan; Arief Mardiyanto; A Azhar; Muhammad Kamal; Atiqah Aida (Politeknik Negeri Lhokseumawe, 2023)
Solar energy has now been converted into electrical energy by using alternative solar panels to absorb heat energy which is converted into electrical energy. Solar panels or often referred to as photovoltaic systems are an alternative that is being actively developed to deal with the global status of energy shortages because fossil energy sources, which have been the main energy source, will run out as population growth increases. In this study used a solar cell with a capacity of 100 Wp which required 27 units of solar cells. used solar. The absorption power of the solar cell energy used is 2,500 watts with varying operating times, namely 1.5 hours, 3 hours, 4.5 hours and 6 hours. The use of solar cell energy will later be used for agarwood oil distillation. Gaharu wood is pre-treated in the form of drying and soaking before the distillation process is carried out. Pretreatment is carried out with the aim that the resulting essential oil can increase in yield. The results obtained yield showed the best quality at the 20th day immersion time and 10 hours of distillation time (0.51%). The results of the GC-Ms gas chromatogram analysis were indicated by the presence of guaiol, selinene and panasinsen compounds, namely (55.90%), (19.56%) and (5.53%).Â Keywords: solar cell, renewable energy, agarwood, distillation